2013
DOI: 10.1177/2158244013497725
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Assessment of Higher Education Access, Participation, Equity, and Disparity in Ghana

Abstract: Since independence, Ghana has comparatively distinguished itself among many Sub-Saharan African (SSA) countries in its educational developments. Tertiary education in Ghana over the past decade has witnessed tremendous growth in various frontages-increased access and participation, relative expansion of academic facilities, a growing private sector, and most importantly, a transformative policy environment. Despite these overwhelming developments, there remain inequalities in the higher education system in Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 14 publications
4
61
0
2
Order By: Relevance
“…Increased rural-urban migration has also brought millions of people living in rural areas to the urban centers. Variations in teacher-student ratios, human resource capacity, provision of educational infrastructure, and other facilities have also led to rural, urban, and regional differences in educational opportunities in different parts of Ghana (Atuahene & Owusu-Ansah, 2013;Banson, 2010;Osei-Mensah, 2012;Owusu-Afriyie, 2009; The President's Committee on Review of Education Reforms in Ghana, 2002;Siaw, 2009).…”
Section: Rural-urban Disparitiesmentioning
confidence: 99%
“…Increased rural-urban migration has also brought millions of people living in rural areas to the urban centers. Variations in teacher-student ratios, human resource capacity, provision of educational infrastructure, and other facilities have also led to rural, urban, and regional differences in educational opportunities in different parts of Ghana (Atuahene & Owusu-Ansah, 2013;Banson, 2010;Osei-Mensah, 2012;Owusu-Afriyie, 2009; The President's Committee on Review of Education Reforms in Ghana, 2002;Siaw, 2009).…”
Section: Rural-urban Disparitiesmentioning
confidence: 99%
“…Atuahene and Owusu-Ansah (2013) further argue that largest population of students in higher education originates from urban regions and cities with highly resourced and facilitated high schools. Such institutions enhance the affordability of the rich depriving the poor from attending such schools.…”
Section: International Journal Of Research Studies In Education 21mentioning
confidence: 99%
“…This has greatly created a huge vacuum between the rich and the poor making education in Ghana more of a privilege than a right. Although several studies have been conducted on accessibility of higher education in Ghana (Atuahene, 2014;Atuahene & Owusu-Ansah, 2013;Dadzie, 2009;Amenyah, 2009), much has not been done on whether university education is a privilege or right.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for more lucrative jobs and higher positions within the workplace has augmented the need for higher learning as well as learning while working (Atuahene & Owusu-Ansah, 2013). This research study was conducted to find solutions to the problems identified by universities in general but with special emphasis to those in Ghana.…”
Section: The Research Problemmentioning
confidence: 99%